Gender Empowerment, Supply-Chain Linkages and Foreign Direct Investment: Evidence on Bangladesh - Ana Margarida Fernandes; Hiau-Looi Kee (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This paper studies foreign direct investment (FDI) spillovers on gender labor market practices of domestic firms, based on a unique firm-to-firm dataset of Bangladesh's textiles and garment sectors. We look at the female employment of domestic firms that are directly and indirectly related to the FDI firms through supply chain linkages. These domestic firms are either the local suppliers or customers of FDI firms or they share local suppliers and customers with the FDI firms. The estimates show that domestic firms related to FDI firms have significantly more female administrative workers, but not necessarily female non-administrative workers, due to more firm-to-firm interactions participated by the former.
Keywords: F10; F20; F60; J20; 330; foreign direct investment; women; female labor force participation; supply chain linkages; Bangladesh